Medial and Lateral Meniscus Posterior Root Tears with an Intact Anterior Cruciate Ligament - Yuki Okazaki; Takayuki Furumatsu; Yuya Kodama; Yoshinori Matsumoto; Motoki Takahashi; Toshifumi Ozaki (Case Reports in Orthopedics)
Background. Medial meniscus (MM) posterior root tear (PRT) is often caused by meniscal degeneration, whereas lateral meniscus (LM) PRT is mainly caused by trauma, especially trauma associated with anterior cruciate ligament (ACL) injuries. Although there are a few reports on PRTs of both menisci with an ACL injury, to our knowledge, there is no report on those with an intact ACL. Thus, the purpose of this study was to describe a rare case of both meniscal PRTs with an intact ACL. Case Presentation. A 67-year-old woman complained of right knee pain during weeding in a deep knee flexion position. At presentation, three days after the injury, physical examination revealed signs of meniscal injury without ACL rupture. Magnetic resonance imaging showed PRTs of both menisci and damaged cartilage, especially on the medial femoral condyle and lateral tibial plateau. MM was sutured using the FasT-Fix dependent modified Mason-Allen suture technique, and LM by a single simple stitch using the Knee Scorpion suture passer. Referring to previous cadaveric studies, transtibial pullout repair using a single tibial tunnel for MM fixation was performed. The stability of the repaired menisci was checked by probing during second-look arthroscopy at one year after the primary surgery, and no meniscal signs and symptoms were present at the last follow-up one year after the surgery. Conclusions. This rare case showed PRTs of both menisci with an intact ACL. We speculated that, in this case, both roots tore because of the degenerative menisci. A good clinical outcome was achieved after single-transtibial pullout repair. This technique may be an effective surgical approach for PRTs of both menisci.